Understanding the Char-Bending Technique in Shipwreck Planks - Bram, Moshe; Me-Bar, Yoav (Heritage, 2023)
Char-bending is a term used in marine archaeology literature to describe the process of shaping long hull components (planks, wales, stringers) by bending them over open fire, from Antiquity, up to modern times. Experiments were done on planks of two wood species with different cross-sections. The planks were heated over open fire while monitoring the internal temperature and charred layer thickness on the side of the plank facing the heat source. The results show that in order to reach the temperature inside the wood required for it to become pliable, the formation of a charred layer, an undesirable by-product, is unavoidable. It is explained why char-bending, in almost all cases, occurs on the concave side of the plank.